ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIK SISWA SMP KELAS VII PADA MATERI BANGUN DATAR - Asep Tantowi; Euis Eti Rohaeti; M Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to determine the level of ability of mathematical understanding of junior high school students VII in Karawang on the matter of building flat. The type of research used is a qualitative descriptive research. Sempel in this research is students of SMP Negeri 1 Batujaya. The data collected in the form of written test results as much as 5 items that refer to the ability of students' mathematical understanding. Most students can not understand what the problem wants. Based on the results of research students average percentage of results from the test description is only reached 58%. Judging from the test results can be said that students' mathematical understanding ability is still low.